AI-based system for automated project estimation in the printing industry - Kostaryev, D.; Tkachenko, V.; Sizova, N. (Advertising and Media Centre of Kauno kolegija Higher Education Institution Layout Virginijus Valčiukas, 2025)
Modern printing companies face increasing demand for personalized, short-run, and fast-turnaround orders. In such a dynamic environment, accurate and rapid estimation of project cost, production time, and required materials is critical for maintaining profitability and customer satisfaction.
Keywords: AI estimation system; printing industry